The Effectiveness of the State Budget in Poverty Alleviation in Indonesia:: A Comparative Study of Government Regimes 1990-2024 - Dedi Junaedi; Muhammad Rizal Arsyad; Faisal Salistia; Siti Aulia Rahmatussyifa; Rio Kartika Supriyatna; Muhammad Taufik Ikramullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effectiveness of budget use (APBN), foreign debt and differences in government regimes in poverty alleviation in Indonesia. The research method used is quantitative analysis of multiple regression with dummy variables. The results of the study indicate: simultaneously, the amount of APBN, Foreign Debt, Inflation and differences in government regimes have a positive impact on poverty alleviation efforts in Indonesia. Partially, the APBN variable (at α 5%) has a significant effect on efforts to reduce poverty rates. Foreign debt, inflation, Era1, Era2, Era3, Era4, and Era5 have no significant effect on poverty rates. If the standard error is increased (up to α 30%), then Era4 and Era5 also have a significant effect on poverty rates with negative coefficient values. While the inflation and Era1 variables are positively correlated with poverty rates. The statistically valid econometric model is as follows:%POOR = 0.180713842147 – 0.000021076*APBN - 0.02057*ERA4 - 0.0301788*ERA5 Keywords: APBN Effectiveness, Indonesian Government Regime, Foreign Debt